The Innovative Strategies in Islamic Education Management to Improve Learning Quality in the Era of Disruption - Linda Nevia Sari; Idi Warsah; Jumira Warlizasusi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research aims to analyze innovative strategies in Islamic education management to improve the quality of learning in the era of disruption. The method used in this research is a literature study by reviewing various sources related to innovation in Islamic education management, especially related to the use of technology. The results show that technology-based learning, such as e-learning through Learning Management System (LMS), is the main strategy to improve the quality of Islamic education. This technology provides flexibility in learning access and allows students to learn anytime and anywhere. However, some constraints such as limited access to technological devices and uneven internet connections remain a challenge. In addition, teachers' proficiency in using technology is an important factor for the success of technology-based learning. Cooperation between Islamic education institutions and the technology and industry sectors is also an important strategy in accelerating technology integration and ensuring a curriculum that is relevant to industry demands. Student-centered learning strategies have also proven effective in improving student engagement and mastery of the material. Improving students' digital literacy is also an important aspect in facing information challenges in the era of disruption. This study concludes that by adopting technology wisely and making it.